Tata bahasa acuan bahasa Indonesia untuk penutur asing - Kentjono, Djoko; Datang, Frans Asisi (Jakarta : Wedatama Widya Sastra, 2010)
Grammar of Indonesian language for foreign speakers.
Mengandungi daftar pustaka (mukasurat 251-252).
Keywords: Indonesian language -- Grammar; Indonesian language -- Study and teaching -- Foreign speakers